Effectiveness of Audiovisual Nutrition Education via YouTube on Balanced Nutrition Knowledge and Attitudes Among Indonesian Adolescents: A Quasi-Experimental Study - Tamara, Metha Dwi; Ruhyat, Ejeb; Tusrini, Weni; Effendi, Julham; Tania Fidzikri, Nanda Berliana; Yamin, Imam Syahputra; Rahmawati, Santi Deliani (Rifa'Institute, 2026)
Introduction: Adolescents currently face a double burden of malnutrition amidst a rapid transformation in digital health information. Conventional educational methods often fail to effectively engage Generation Z, a demographic with a distinct preference for visual and interactive learning formats. Objective: This study evaluated the effectiveness of a YouTube-based audiovisual intervention in improving knowledge and attitudes regarding balanced nutrition among adolescents in a boarding school setting. Method: This quantitative study employed a quasi-experimental, one-group pretest-posttest design. Participants comprised 88 students from MAPK Jabal Hikmah, an Islamic boarding school in East Lombok Regency, Indonesia, recruited via total sampling. The intervention consisted of a structured educational video aligned with the Indonesian Balanced Nutrition Guidelines (Pedoman Gizi Seimbang). Data were analyzed using the Wilcoxon Signed-Rank Test due to the non-normal distribution of variables. Result and Discussion: The intervention yielded a statistically significant increase in nutrition knowledge (p < 0.001), with mean scores rising from 30,51 to 80,40. Attitude scores also demonstrated significant improvement (p < 0.001), increasing from 46,53 to 61,02. Notably, the proportion of students categorized as having a